FAKTOR – FAKTOR PENDORONG MAHASISWA MEMILIH BERKARIR SEBAGAI KONSULTAN PAJAK (Studi Empiris Mahasiswa S1 Akuntansi) - Intan Rahma Sari; Aura Zahra Al Januar; Nayla Regita Cahyani; Sri Putri Winingrum W.A; Muliyani (LPPM STIE YKPN Yogyakarta, 2026)
This study aims to examine the influence of motivation, self-efficacy, and taxation knowledge on accounting students’ interest in pursuing a career as tax consultants. This research employs a quantitative approach with purposive sampling. Data were collected through questionnaires distributed to 100 accounting students. The independent variables in this study are motivation, self-efficacy, and taxation knowledge, while the dependent variable is career interest as a tax consultant. Multiple linear regression analysis is used to assess the relationship between the independent and dependent variables. The findings indicate that motivation, self-efficacy, and taxation knowledge significantly and positively affect students’ interest in pursuing a career as tax consultants.